Hadith #59 - Sunan al-Nasa'i - Abu Hurairah; al-Mughira bin Abi Burda المغيرة بن أبي بردة; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Salmah bin Aby سعيد بن سلمة بن أبي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan al-Nasa'i)
“A man asked the Prophet (ﷺ): ‘O Messenger of Allah, we travel by sea and we take a little water with us, but if we use it for Wudu’, we will go thirsty. Can we perform Wudu’, with sea-water?’ The Messenger of Allah (ﷺ) said: ‘Its water is a means of purification and its dead meat is permissible.'”
Grade:

Hadith #332 - Sunan al-Nasa'i - Abu Hurairah; al-Mughira bin Abi Burda المغيرة بن أبي بردة; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Salmah bin Aby سعيد بن سلمة بن أبي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘None of you should perform Ghusl in standing water while he is Junub.'”
Grade:

Hadith #409 - Sunan al-Nasa'i - Abu Hurairah; Ahmed bin Hafs bin 'Abdullah أحمد بن حفص بن عبد الله; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hafs bin 'Abdullah bin Rashid حفص بن عبد الله بن راشد; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Musa bin 'Uqba موسى بن عقبة; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan al-Nasa'i)
“I put some water out for the Messenger of Allah (ﷺ), then I concealed him” – and she mentioned how he performed Ghusl, then she said: “Then I brought him a cloth (a towel) but he did not want it.”
Grade:

Hadith #748 - Sunan al-Nasa'i - Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Nafi' bin Jubayr bin Mut'im نافع بن جبير بن مطعم; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Sahl bin Abi Hathma; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan al-Nasa'i)
“The messenger of Allah(ﷺ) was asked during the campaign of Tabuk about the Sutra of one who is praying. He said: “Something as high as the back of a camel saddle.”
Grade:

Hadith #3111 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Hurairah; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Hammad bin Salama حماد بن سلمة; Khalid bin al-Lajlaj al-Amiri خالد بن اللجلاج العامري; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan al-Nasa'i)
“O Messenger of Allah! Which of the people is best?” He said: “One who strives with himself and his wealth in the cause of Allah.” He said: “Then who, O Messenger of Allah?” He said: “Then a believer (isolating himself) in one of the mountain passes, who fears Allah and spares the people his evil.”
Grade:

Hadith #4350 - Sunan al-Nasa'i - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Hurairah; al-Mughira bin Abi Burda المغيرة بن أبي بردة; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Sa'id bin Salmah bin Aby سعيد بن سلمة بن أبي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan al-Nasa'i)
“The Messenger of Allah reached Khaibar in the morning, and they came out to us carrying their shovels. When they saw us they said: ‘Muhammad and the army!’ And they rushed back inot the fortress. The Messenger of Allah raised his hands, then he said: ‘ Allahu Akbar, Allahu Akbar, Khaibar is destroyed. Verily, when we descend in field of a people (i.e. near to them), evil will be the morning for those who had been warned! Acquired some donkeys there and we cooked the., Then the caller of
Grade:

Hadith #4862 - Sunan al-Nasa'i - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Muhammad bin al-Mubarak محمد بن المبارك; Muhammad bin Mus'ab bin Sdqh محمد بن مصعب بن صدقة; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan al-Nasa'i)
“When the Messenger of Allah (ﷺ) conquered Makkah , he said in his Khutbah: ‘For any wound that exposes the bone, the diyah is five (camels) each.'”
Grade:

Hadith #5127 - Sunan al-Nasa'i - Abu Hurairah; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin Isma'il bin Ibrahim محمد بن إسماعيل بن إبراهيم بن مقسم; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan al-Nasa'i)
The Prophet said: “The perfume for men is that whose scent is apparent while its color is hidden, and the perfume for women is that whose color is apparent, while its scent is hidden.”
Grade:

Hadith #5427 - Sunan al-Nasa'i - Abu Hurairah; Ahmed bin Hafs bin 'Abdullah أحمد بن حفص بن عبد الله; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hafs bin 'Abdullah bin Rashid حفص بن عبد الله بن راشد; Ibrahim bin Tahman إبراهيم بن طهمان; Musa bin 'Uqba موسى بن عقبة; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan al-Nasa'i)
“A man among the Ansar stated that his salve was to be set free after he died; he was in need, and he owed a debt. The Messenger of Allah sold him (the slave) for eight hundred Dirhams, and he gave (the money) to him and said: ‘Pay off your debt and spend on your dependents.'”
Grade:

Hadith #2130 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Hassan ibn Ali bin Abi Talib; Ibn Jurayj ابن جريج; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan Abi Dawud)
When the Prophet (ﷺ) congratulated a man on his marriage, he said: May Allah bless for you, and may He bless on you, and combine both of you in good (works).
Grade: Sahih

Hadith #2432 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Umar bin Thabit عمر بن ثابت الأنصاري (Sunan Abi Dawud)
I asked or someone asked the Prophet (ﷺ) about perpetual fasting. He replied: You have a duty to your family. Fast during Ramadan and the following month, and every Wednesday and Thursday. You will then have observed a perpetual fast.
Grade: Da'if

Hadith #3051 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Probably you will fight with a people, you will dominate them, and they will save themselves and their children by their property. The version of Sa’id has You will then conclude peace with them. The agreed version goes: Then do no take anything from them more than that, for it is not proper for you.
Grade: Da'if

Hadith #69 - Jami' al-Tirmidhi - Abu Hurairah; al-Mughira bin Abi Burda المغيرة بن أبي بردة; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ma'n bin 'Isa bin Yahya معن بن عيسى بن يحيى; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Salmah bin Aby سعيد بن سلمة بن أبي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Jami' al-Tirmidhi)
“A man asked Allah’s Messenger ‘O Messenger of Allah! We sail the seas, and we only carry a little water with us. If we use it for Wudu then we will go thirsty. So shall we perform Wudu from the (water of the) sea?’ Allah’s Messenger said: ‘Its water is pure, and its dead are lawful.'”
Grade:

Hadith #550 - Jami' al-Tirmidhi - al-Bara' bin Azib bin al-Harith; al-Laith bin Sa'd الليث بن سعد; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Jami' al-Tirmidhi)
“I accompanied the Messenger of Allah on eighteen journeys, and I did not see him leave the two Rak’ah when the sun waned before Zuhr.”
Grade:

Hadith #1457 - Jami' al-Tirmidhi - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abu al-Darda; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Jami' al-Tirmidhi)
(Another chain) from An-Nu’man bin Bashir with similar.
Grade:

Hadith #250 - Sunan Ibn Majah - Abu Hurairah; al-Hasan al-Basri الحسن البصري; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني (Sunan Ibn Majah)
“I saw Sa’ib bin Yazid sniffing his garment, and I said: ‘Why (are you doing) that?’ He said: ‘I heard the Messenger of Allah say: “No ablution (is needed) unless there is an odor or a sound.”
Grade:

Hadith #277 - Sunan Ibn Majah - Abdur Rahman bin Abi Sa'id al-Khudri عبد الرحمن بن أبي سعيد; Abu Sa'id al-Khudri; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan Ibn Majah)
“Jarir bin ‘Abdullah urinated, then he performed ablution and wiped over his leather socks. Someone asked him: ‘Do you do this?’ He said: ‘Why shouldn’t I? I saw the Messenger of Allah doing this.'” Ibrahim (who narrated it from Hammam) said: “They were pleased by the Hadith of Jarir because he accepted Islam after the revelation of Ma’idah.”
Grade:

Hadith #417 - Sunan Ibn Majah - Abu Hurairah; al-Mughira bin Abi Burda المغيرة بن أبي بردة; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'id bin Salmah bin Aby سعيد بن سلمة بن أبي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan Ibn Majah)
“The Prophet prayed the ‘Asr when the sun was shining into my room and there were no shadows yet.”
Grade:

Hadith #1142 - Sunan Ibn Majah - Abu Sa'id al-Khudri; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله; Sahl bin Znjlh سهل بن زنجلة; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“When Sulaiman bin Dawud finished building Baitil-Maqdis, he asked Allah for three things: judgment that was in harmony with His judgment, a dominion that no one after him would have, and that no one should come to this mosque, intending only to pray there, but he would emerge free of sin as the day his mother bore him.” The Prophet (ﷺ) said: “Two prayers were granted, and I hope that the third was also granted.”
Grade:

Hadith #2318 - Sunan Ibn Majah - Abu Usayd Malik bin Rabi'a; Ibrahim bin al-Mandhir bin 'Abdullah إبراهيم بن المنذر بن عبد الله; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘If a man’s property is wrongfully targeted, and he is killed, he is a martyr.”
Grade:

Hadith #3367 - Sunan Ibn Majah - Abu Hurairah; al-Mughira bin Abi Burda المغيرة بن أبي بردة; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'id bin Salmah bin Aby سعيد بن سلمة بن أبي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan Ibn Majah)
“I used to part the hair of the Messenger of Allah (ﷺ) behind his crown, and let his forelock hang down.”
Grade: